PENGEMBANGAN TEKNOLOGI PEMBUATAN BIOPOLIMER BERNILAI EKONOMI TINGGI DARI LIMBAH TANAMAN JAGUNG (Zea Mays) UNTUK INDUSTRI MAKANAN: CMC (CARBOXYMETHYLCELLULOSE) - Lestari, Puji; Hidayati, Titi Nur; Lestari, Siti Hanum Indah; Marseno, Djagal Wiseso (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Corncobs is agricultural waste that have ascent amounts every years. The purposes of this research were to obtain information cellulose alternative source from corncobs for material of CMC; get optimum condition of synthesis CMC with food grade of DS and the characteristic of pH, viscosity, purity CMC. Synthesis CMC through alkalization and carboxymethylation process. The variation of NaOH concentration are 7,93; 10,00; 15,00; 20,00; 22,07% in alkalization and variations amount of NaMCA are 4,5858; 5,0000; 6,0000; 7,0000; 7,4142 Â gram in carboxymethylation. The result was cellulose content in corncobs is 62,80 %. The optimum condition which obtained from 15% NaOH and 5,04 g NaMCA gave CMC with DS 0, 82 ; pH 7,64 ; purity 99,52 % ; and viscosity 25,40 cps. Â Keywords: CMC, corncob, DS